Triaging transient ischemic attack and minor stroke patients using acute magnetic resonance imaging. - Coutts, S; Simon, J; Eliasziw, M; Sohn, C; Hill, MD; Barber, P; Palumbo, V; Kennedy, J; Roy, J; Gagnon, A; Scott, J; Buchan, A; et al. (2005)
We examined whether the presence of diffusion-weighted imaging (DWI) lesions and vessel occlusion on acute brain magnetic resonance images of minor stroke and transient ischemic attack patients predicted the occurrence of subsequent stroke and functional outcome. 120 transient ischemic attack or minor stroke (National Institutes of Health Stroke Scale < or = 3) patients were prospectively enrolled. All were examined within 12 hours and had a magnetic resonance scan within 24 hours. Overall, the 90-day risk for recurrent stroke was 11.7%. Patients with a DWI lesion were at greater risk for having a subsequent stroke than patients without and risk was greatest in the presence of vessel occlusion and a DWI lesion. The 90-day risk rates, adjusted for baseline characteristics, were 4.3% (no DWI lesion), 10.8% (DWI lesion but no vessel occlusion), and 32.6% (DWI lesion and vessel occlusion) (p = 0.02). The percentages of patients who were functionally dependent at 90 days in the three groups were 1.9%, 6.2%, and 21.0%, respectively (p = 0.04). The presence of a DWI lesion and a vessel occlusion on a magnetic resonance image among patients presenting acutely with a transient ischemic attack or minor stroke is predictive of an increased risk for future stroke and functional dependence.